2021
DOI: 10.33448/rsd-v10i14.21981
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temporomandibular disorder on oral health-related quality of life in adolescents

Abstract: The aim of this cross-sectional study was to assess the impact of temporomandibular disorder (TMD) on oral health-related quality of life (OHRQoL) of adolescents. The OHRQoL of adolescents undergoing dental treatment at a University clinic in 2019 was measured using the Brazilian version of the Oral Heath Impact Profile – 14 (OHIP-14). The diagnosis of TMD was performed using Research Diagnostic Criteria for Temporomandibular disorders (RDC/TMD). The patients were examined for other oral conditions and the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Notwithstanding the inadequacies in cleaning the posterior teeth, therefore, they are the most exposed teeth to the dental cavity. This study is in line with the previous studies [13][14] [23] where the tooth structure differs and as such the posterior teeth structure has pits and fissures on the occlusal surface is more susceptible to dental caries attacks than the anterior teeth. This study showed that the posterior attacks were dominant at the molars whose results concur with the findings by Innes et al [13].…”
Section: Dental Cariessupporting
confidence: 92%
“…Notwithstanding the inadequacies in cleaning the posterior teeth, therefore, they are the most exposed teeth to the dental cavity. This study is in line with the previous studies [13][14] [23] where the tooth structure differs and as such the posterior teeth structure has pits and fissures on the occlusal surface is more susceptible to dental caries attacks than the anterior teeth. This study showed that the posterior attacks were dominant at the molars whose results concur with the findings by Innes et al [13].…”
Section: Dental Cariessupporting
confidence: 92%